Answer:
The answer is2nd point
Step-by-step explanation:
![{n}^{a} \times {n}^{b} = {n}^{a + b}](https://tex.z-dn.net/?f=%20%7Bn%7D%5E%7Ba%7D%20%20%5Ctimes%20%20%7Bn%7D%5E%7Bb%7D%20%20%3D%20%20%7Bn%7D%5E%7Ba%20%2B%20b%7D%20)
(x^4/3)×(x^2/3) = x^(4/3 + 2/3)
= x²
![{( {n}^{a} )}^{b} = {n}^{ab}](https://tex.z-dn.net/?f=%20%7B%28%20%7Bn%7D%5E%7Ba%7D%20%29%7D%5E%7Bb%7D%20%20%3D%20%20%7Bn%7D%5E%7Bab%7D%20)
(x²)^1/3 = x^(2×1/3)
= x^2/3
The area of a circle is A = πr^2. We let A1 And A2 the areas of the circles and r1 and r2 the radius of each, respectivley.
A1 + A2 = 80π
Substitute the formula for the area,
π(r1)^2 + π (r2)^2 = 80π
From the statement, we know that r2=2(r1).
<span>π(r1)^2 + π (2 x r1)^2 = 80π
</span>We can cancel π, we will have
5 x (r1)^2 = 80
Thus,
r1 = 4 and r2 = 8
I have already done this question. The correct answer is c